Analysis Of The Influence Of Economic Value Added, Market Value Added, And Return On Investment On Stock Return With Company Value As Intervening Variables In Agricultural Sub Sector Companies Plantations - Dwi Setiyawan; Andini Nurwulandari (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of Economic Value Added, Market Value Added, and Return On Investment on stock returns mediated by firmvalue. The population of this study were 10 companies listed on the Indonesia Stock Exchange in the Agriculture Companies of the Plantation Sub-Sector. The analytical method used is descriptive analysis with Smart PLS v3.0 software. The results of this study indicate that: 1) Economic Value Added has a negative andinsignificant effect on firm value; 2) Market Value Added has a positive andsignificanteffectonCompanyValue; 3)Return on Investment has a positive and significant effect on Firm Value; 4) Economic Value Added has a negativeand insignificant effect on Stock Return; 5) Market Value Added has a positive and insignificant effect on Stock Return; 6) Return on Investment has a positiveand significant effect on Stock Return; 7) Economic Value Added has a positiveand insignificant effect on Stock Return through Company Value; 8) Market Value Added has a negative and insignificant effect on Stock Return through Company Value; 9) Return On Investment has a negative and insignificant effecton Stock Return through Company Value; 10) Firm Value has a negative andinsignificant effect on Stock Return. Agricultural companies in the plantation sub-sector need to pay attention to the value creation and use of their capital.